Polynomial and Rational Approximations and the Link between Schröder’s Processes of the First and Second Kind - François Dubeau (Abstract and Applied Analysis)
We show that Schröder’s processes of the first kind and of the second kind to obtain a simple root of a nonlinear equation are related by polynomial and rational approximations.